Дані про випуск - (:unkn) unknown (My University, 2018)
Literature and Culture of Polissya. Vol. 91. Series "Philology Research". № 10 / editor-in-chief H. V. Samoylenko. Nizhyn: NDU named after N. Gogol, 2018. 312 p.